Effect of tobacco control policies on perinatal and child health: a systematic review and meta-analysis - Timor Faber, MPH; Arun Kumar, MSc; Prof Johan P Mackenbach, PhD; Prof Christopher Millett, PhD; Sanjay Basu, PhD; Prof Aziz Sheikh, MD; Dr Jasper V Been, PhD (Elsevier, 2017)
Background: Tobacco smoking and smoke exposure during pregnancy and childhood cause considerable childhood morbidity and mortality. We did a systematic review and meta-analysis to investigate whether implementation of WHO's recommended tobacco control policies (MPOWER) was of benefit to perinatal and child health. Methods: We searched 19 electronic databases, hand-searched references and citations, and consulted experts to identify studies assessing the association between implementation of MPOWER policies and child health. We did not apply any language restrictions, and searched the full time period available for each database, up to June 22, 2017. Our primary outcomes of interest were perinatal mortality, preterm birth, hospital attendance for asthma exacerbations, and hospital attendance for respiratory tract infections. Where possible and appropriate, we combined data from different studies in random-effects meta-analyses. This study is registered with PROSPERO, number CRD42015023448. Findings: We identified 41 eligible studies (24 from North America, 16 from Europe, and one from China) that assessed combinations of the following MPOWER policies: smoke-free legislation (n=35), tobacco taxation (n=11), and smoking cessation services (n=3). Risk of bias was low in 23 studies, moderate in 16, and high in two. Implementation of smoke-free legislation was associated with reductions in rates of preterm birth (-3·77% [95% CI −6·37 to −1·16]; ten studies, 27 530 183 individuals), rates of hospital attendance for asthma exacerbations (-9·83% [-16·62 to −3·04]; five studies, 684 826 events), and rates of hospital attendance for all respiratory tract infections (-3·45% [-4·64 to −2·25]; two studies, 1 681 020 events) and for lower respiratory tract infections (-18·48% [-32·79 to −4·17]; three studies, 887 414 events). Associations appeared to be stronger when comprehensive smoke-free laws were implemented than when partial smoke-free laws were implemented. Among two studies assessing the association between smoke-free legislation and perinatal mortality, one showed significant reductions in stillbirth and neonatal mortality but did not report the overall effect on perinatal mortality, while the other showed no change in perinatal mortality. Meta-analysis of studies on other MPOWER policies was not possible; all four studies on increasing tobacco taxation and one of two on offering disadvantaged pregnant women help to quit smoking that reported on our primary outcomes had positive findings. Assessment of publication bias was only possible for studies assessing the association between smoke-free legislation and preterm birth, showing some degree of bias. Interpretation: Smoke-free legislation is associated with substantial benefits to child health. The majority of studies on other MPOWER policies also indicated a positive effect. These findings provide strong support for implementation of such policies comprehensively across the world. Funding: Chief Scientist Office Scotland, Farr Institute, Netherlands Lung Foundation, Erasmus MC.